Genetic Dielectric Genes Inside 2D Carbon‐Based Materials with Tunable Electromagnetic Function at Elevated Temperature. Issue 11 (27th September 2021) - Cao, Mao-Sheng; Shu, Jin-Cheng; Wen, Bo; Wang, Xi-Xi; Cao, Wen-Qiang
Abstract : Understanding the nature of dominating electromagnetic response and energy conversion is quietly pivotal to achieve tunable electromagnetic function at elevated temperature. Herein, the dielectric genes, especially genetic genes, inside 2D carbon‐based materials are deeply dissected based on previous work, and the contribution of conduction and relaxation to electromagnetic response is highly excavated. The evolution of dielectric genes related to ferroferric oxide (Fe3 O4 ) content, temperature, and spatial distribution is described in detail, which creates an available approach for tunable microwave absorption performance. At 373 K, the 20 wt% product realizes the optimal reflection loss of −59 dB, with a small matching thickness of 1.17 mm. In the coming fifth‐generation (5 G) era, the cognition on dielectric genes furnishes a solid platform for the design and manufacture of high‐efficiency electromagnetic functional materials and devices, vigorously promoting the research of electromagnetic protection in high‐temperature environment. Abstract : Understanding the genetic dielectric genes that dominate electromagnetic response and energy conversion opens up a new horizon for flexible manipulation of electromagnetic function at room temperature and even elevated temperature.